2010
DOI: 10.1002/app.32953
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle structure on the peel strength and heat resistance properties of vinyl acetate/acrylate latexes laminating adhesives

Abstract: The concept of using particle structure design to prepare emulsion laminating adhesives (LAs) for improving both the peel strength and heat resistance properties has been investigated. The homogeneous particle latices based on vinyl acetate/acrylate copolymer (samples 1-3) were synthesized by seeded semicontinuous emulsion polymerization with different chain transfer agent (CTA) contents but with no functional monomers, while the coreshell structure crosslinkable latices (samples 4 and 5) were prepared through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…However, as for conventional emulsion, there are still some deficiencies. A major one is its low peel strength [8,13,14] arising from the competition among film formation, wetting and mechanical film properties [15,16] especially at high temperatures, which limits its further application in the field of adhesives greatly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as for conventional emulsion, there are still some deficiencies. A major one is its low peel strength [8,13,14] arising from the competition among film formation, wetting and mechanical film properties [15,16] especially at high temperatures, which limits its further application in the field of adhesives greatly.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, with increasing attentions of public and government to environmental issues, solvent based laminating adhesives (LAs) used widely in plastic flexible packaging [1][2][3][4] are gradually being replaced by emulsion Las [5][6][7][8] due to the decreased emission of volatile organic compounds [9,10] and low cost [8,11,12] of the latter. However, as for conventional emulsion, there are still some deficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…They found that small latex particles gave adhesive films with a higher peel force at short adhesion times, whereas adhesive films from larger particles required more time to achieve their ultimate peel force. 17,18 However, few researchers have paid attention to the effect of NaHCO 3 on the peel strength of the PSAs. They found that the peel adhesion decreased with the MMA content; this was attributed to a reduction in the ability of the adhesive to wet the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Such composite materials are widely used in various areas. For example, polymer–polymer core–shell particles can be used as effective structures for applications in pigments, fibers, immunological studies, drug delivery systems, baroplastic processing, toughening polymeric materials, transparent conductive thin films, coatings, and adhesives . The combined properties of core and shell polymers are superior to mechanical blends of those polymers.…”
Section: Introductionmentioning
confidence: 99%